2016
DOI: 10.1007/s10803-016-2843-0
|View full text |Cite
|
Sign up to set email alerts
|

Using the PDD Behavior Inventory as a Level 2 Screener: A Classification and Regression Trees Analysis

Abstract: In order to improve discrimination accuracy between Autism Spectrum Disorder (ASD) and similar neurodevelopmental disorders, a data mining procedure, Classification and Regression Trees (CART), was used on a large multi-site sample of PDD Behavior Inventory (PDDBI) forms on children with and without ASD. Discrimination accuracy exceeded 80 %, generalized to an independent validation set, and generalized across age groups and sites, and agreed well with ADOS classifications. Parent PDDBIs yielded better results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The partitioning procedure is repeated recursively at each node. The General Regression and Classification Trees module from the Statistica 12 package (Dell, 2015) was used (where more details about its methods can be found), and more details regarding how the analysis was carried out for the current study can be found in Cohen et al (2016). Domains from the PDDBI and whether the (Cohen & Sudhalter, 2005).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The partitioning procedure is repeated recursively at each node. The General Regression and Classification Trees module from the Statistica 12 package (Dell, 2015) was used (where more details about its methods can be found), and more details regarding how the analysis was carried out for the current study can be found in Cohen et al (2016). Domains from the PDDBI and whether the (Cohen & Sudhalter, 2005).…”
Section: Participantsmentioning
confidence: 99%
“…When using ASD-specific instruments such as the PDDBI to aid in diagnosis, sensitivity (agreement of the instrument with clinical diagnosis of ASD) and specificity (agreement of the instrument with clinical diagnosis of not ASD) are of importance. However, as noted previously (Cohen et al, 2016), these metrics depend, in part, on the degree to which the person being diagnosed displays behaviors that relate to ASD or to behaviors typical of disorders that can overlap with ASD, for example, social anxiety, obsessivecompulsive behaviors, language delay, and so on (Eaves, Wingert, Ho, & Mickelson, 2006;Havdahl, von Tetzchner, Huerta, Lord, & Bishop, 2016;Muratori et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Accuracy depends on achieving an ideal balance of sensitivity (the measure's ability to correctly recognize the presence of a disorder) and specificity (the ability of a measure to correctly recognize when a disorder is absent). Numerous studies have examined the efficacy of screening measures in ASD [e.g., Cohen et al, ]. In sum, these have typically found that the efficacy varies depending on several factors, including whether it's Level 1 or Level 2, broadband or narrowband, the content of the tool, the age range that is being targeted, and what aspect is being optimized (e.g., sensitivity or specificity).…”
Section: Introductionmentioning
confidence: 99%